2012
DOI: 10.2337/db12-0138
|View full text |Cite
|
Sign up to set email alerts
|

Neuroadrenergic Dysfunction Along the Diabetes Continuum

Abstract: Neuroadrenergic function in type 2 diabetic (T2D) patients without neuropathy is poorly characterized. We therefore compared sympathetic nervous system activity at rest and during an oral glucose tolerance test in obese metabolic syndrome (MetS) subjects classified as glucose intolerant (impaired glucose tolerance [IGT]; n = 17) or treatment-naive T2D (n = 17). Untreated subjects, matched for age (mean 59 ± 1 year), sex, BMI (32.4 ± 0.6 kg/m2), and family history of diabetes were studied. We measured resting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 52 publications
(70 reference statements)
4
75
2
2
Order By: Relevance
“…This suggests that chronic marked hyperinsulinaemia may prevent further enhancement of cardiac sympathetic tone during an acute rise in insulin. A similar trend towards a limited increase in sympathetic activity in obese and type 2 diabetic patients has been reported during other tests, including deep breathing, exercise and oral glucose challenge [12,39,40], suggesting a reduction in sympathetic reserve when sympathetic activity is relatively high at baseline. A blunted sympathetic response may result from impaired insulin transport across the blood-brain barrier, which has been shown in experimentally induced insulin resistance in dogs [41], and from lower cerebrospinal fluid insulin levels, as reported in obese insulin-resistant humans [42].…”
Section: Effects Of Insulin On Vagosympathetic Activitymentioning
confidence: 48%
See 1 more Smart Citation
“…This suggests that chronic marked hyperinsulinaemia may prevent further enhancement of cardiac sympathetic tone during an acute rise in insulin. A similar trend towards a limited increase in sympathetic activity in obese and type 2 diabetic patients has been reported during other tests, including deep breathing, exercise and oral glucose challenge [12,39,40], suggesting a reduction in sympathetic reserve when sympathetic activity is relatively high at baseline. A blunted sympathetic response may result from impaired insulin transport across the blood-brain barrier, which has been shown in experimentally induced insulin resistance in dogs [41], and from lower cerebrospinal fluid insulin levels, as reported in obese insulin-resistant humans [42].…”
Section: Effects Of Insulin On Vagosympathetic Activitymentioning
confidence: 48%
“…Thus, a vagosympathetic imbalance may occur prior to diabetes as a result of overweight and insulin resistance. This is strongly supported by the recent demonstration that progression to type 2 diabetes is associated with increased central sympathetic drive, blunted sympathetic responsiveness and altered noradrenaline (norepinephrine) disposition [12]. In addition to obesity and diabetes, several factors associated with these conditions, such as insulin, proinsulin, C-peptide, glucose, leptin, adiponectin and NEFA, have been shown to affect the autonomic nervous system [13,14].…”
Section: Introductionmentioning
confidence: 53%
“…There are reports of overactivation of the sympathetic system in the pre-diabetic and diabetic condition that further contributes to metabolic abnormalities. Straznicky observed the association of blunted sympathetic responsiveness and insulin resistance, and disturbed sympathetic neurobiology is characterized by augmented resting sympathetic nervous activity and blunted sympathetic responsiveness to oral glucose ingestion [35] .…”
Section: Impaired Calcium Homeostasis and Dysfunction Of Mitochondriamentioning
confidence: 99%
“…Those observations provide evidence of a strong linkage between the activity of the sympathetic nervous system and insulin levels over glucose metabolisms. Straznicky et al [68] reported that the progress from metabolic syndrome to type 2 diabetes might be associated with increased central sympathetic drive, blunted sympathetic responsiveness, and altered norepinephrine disposition.…”
Section: Neurohoromonal Characteristics In Type 2 Diabetes: Insulin Rmentioning
confidence: 99%